FORMAÇÃO DE ILHAS DE CALOR EM CENTROS URBANOS UM ESTUDO DE CASO - Giacomelli, Bruna; Benche, Fabiane; Padilha, Júlia Calvaitis; Eckert, Natalia Hauenstein; Mantovani, Paula Renata Albrecht; Nogueira, Bárbara Tatiane Martins Vieira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The study aims to present the analysis of the urban environment of the central area of the city of Cruz Alta in the state of Rio Grande do Sul in the winter and summer seasons. With the specific objective of revising concepts of urban climate, islands of heat, urbanization and urban development, and through them to make a diagnosis of the climatic conditions in specific points. In order to carry out the research, four points were selected in the city center, and field measurement cards were made, with the purpose of recording the collections on three consecutive days and at different times, in order to prepare the final conclusions. The results reported that there is a need for the application of strategies to shade these spaces, since the temperatures recorded in the shade caused a more favorable climatic condition. One of the indicated strategies would be the implantation of a more significant afforestation, green beds and corridors, solutions that contribute to the reduction of heat in the most built areas.